2012
DOI: 10.1155/2012/598606
|View full text |Cite
|
Sign up to set email alerts
|

Current Pharmacologic Approaches for Prevention and Treatment of Bronchopulmonary Dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is a major complication of preterm birth and has serious adverse long-term health consequences. The etiology of BPD is complex, multifactorial, and incompletely understood. Contributing factors include ventilator-induced lung injury, exposure to toxic oxygen levels, and infection. Several preventive and therapeutic strategies have been developed with variable success. These include lung protective ventilator strategies and pharmacological and nutritional interventions. These st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 89 publications
1
20
0
1
Order By: Relevance
“…Therefore, we suggest that ginger has antiinflammatory properties by decreasing neutrophil activation and migration into the lungs with evidence of reduced MPO activity in the lungs (9,11). Oxygen toxicity has a key role in the development of BPD (1)(2)(3)(4)(5)(6)(7). High concentrations of inspired oxygen can damage lung cells by the overproduction of cytotoxic reactive oxygen species (ROS) such as superoxide free radical, hydrogen peroxide, and hydroxyl free radical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we suggest that ginger has antiinflammatory properties by decreasing neutrophil activation and migration into the lungs with evidence of reduced MPO activity in the lungs (9,11). Oxygen toxicity has a key role in the development of BPD (1)(2)(3)(4)(5)(6)(7). High concentrations of inspired oxygen can damage lung cells by the overproduction of cytotoxic reactive oxygen species (ROS) such as superoxide free radical, hydrogen peroxide, and hydroxyl free radical.…”
Section: Discussionmentioning
confidence: 99%
“…Prematurity is believed to be the most important contributing factor, in addition to other factors, including oxidative stress and inflammationmediated lung injury (chorioamnionitis), hyperoxia/ value-barotrauma, and genetic factors (5,6). Treatment strategies for the prevention of lung injury and appropriate induction of lung growth to avoid the development of BPD are still lacking (3,7). Therefore, new treatment options need to be identified for the prevention of severe injury to the lungs in the course of BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose inhaled nitric oxide failed to reduce the incidence of BPD in very premature infants [8,22]. Further treatment modalities include the administration of caffeine/methylxanthines, diuretics and adequate nutritional support [4,23], and in the future stem cells may play a role in regenerative neonatology [24,25]. …”
Section: Potential Risks and Benefits Of High-dose Vitamin A Supplemementioning
confidence: 99%
“…These studies demonstrated no improvement in mortality, days on mechanical ventilation, or incidence of BPD, arguing against targeting mast cells for mitigating CLD. However, they did not assess drug delivery in these studies, thus failing to provide evidence for effective drug deposition (59). It is feasible that other means of silencing mast cells will be developed that may be therapeutic for ameliorating CLD.…”
Section: Discussionmentioning
confidence: 99%